Some Conditions for the Boundedness of Commutators of Fractional Integrals on Generalized Weighted Morrey Spaces - Ramadana, Yusuf (JURNAL DIFERENSIAL, 2025)
In this paper, we investigate the boundedness of commutators generated by $b\in BMO$ and fractional integrals $I_α$ from $\mathcal{M}_{ψ_1}^{p,w^p}$ to $\mathcal{M}_{ψ_2}^{q,w^q}$ for $1<p<q<∞$. We obtain some new conditions for the pair $(ψ_1,ψ_2)$ of the functions $ψ_1$ and $ψ_2$ on $\mathbb{R}^n× (0,∞)$ that ensure the boundedness properties.